THE IMPACT OF SOCIAL MEDIA ON ENGLISH LEXICAN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article examines the positive and negative impact of social media on the modern English lexicon. It also explores the role of social media in contemporary society and its contribution to the development of English lexicology. In addition, the concept of lexicology, as well as hashtags and internet-specific units such as abbreviations and acronyms, are analyzed with illustrative examples.